Greetings for Eid Al-Fitr 1446 H/2025 Ad in Tolaki Language - Untung; Saasa; Mariyatul Kiptiyah; Darmin (Journal of Law, Social Science and Management, 2025)
Background: Eid al-Fitr is a significant religious celebration among Muslims worldwide, including the Tolaki ethnic group in Southeast Sulawesi, Indonesia. The use of the Tolaki language during this festivity reflects cultural identity and local linguistic preservation.Objectives: This study aims to document and analyze the structure, meaning, and cultural significance of Eid al-Fitr greetings in the Tolaki language during the 1446 H/2025 AD celebration.Methods: A qualitative descriptive approach was employed, involving ethnolinguistic observation, interviews with native speakers, and textual analysis of greeting expressions used during Eid. Participants were selected through purposive sampling from communities in Konawe and Kendari.Results: The findings revealed various forms of Eid greetings in Tolaki, often combining Islamic religious values with local expressions of respect, kinship, and social harmony. The greetings typically begin with religious phrases followed by culturally embedded terms denoting apology, blessings, and communal ties.Conclusion: Eid greetings in the Tolaki language serve as a medium for both religious observance and cultural expression, highlighting the role of language in sustaining local identity during global religious events Keywords: Tolaki language, Eid al-Fitr, greetings, cultural identity, Southeast Sulawesi, ethnolinguistics